Antibacterial activity of Rhizophora apiculata leaf extract against Edwardsiella tarda bacteria - Kurniawan, Ronal (Jurnal Natur Indonesia, 2021)
Aquaculture production is vulnerable to adverse impacts to disease and environmental conditions. One of the pathogenic bacteria that infection cultured is Edwardsiella tarda. The aim of this study was to find out the sensitivity of R.apiculata leaf extract in inhibiting the growth of E.tarda. The research method used is the experimental method, with the Kirby-Bauer disc method. The doses used were 100% (10000 ppm), 90% (9000 ppm), 80% (8000 ppm), 70% (7000 ppm), 60% (6000 ppm), 50% (5000 ppm), 40% (4000 ppm), 30% (3000 ppm), 20% (2000 ppm), 10% (1000 ppm) and control (Oxytetracycline), blank discs used were 6 mm in size. The results showed that the ethanolic extract of the leaves of R. apiculata at a dose of 1000-10000 ppm gave various inhibitory diameters ranging from 6.27-9.87 mm and presenting inhibition zone diameters in the medium category